Manajemen Peningkatan Prestasi Mahasiswa Pada Strategi Model Pembelajaran Kooperatif Team Assisted Individualization - Masbullah (Journal of International Multidisciplinary Research, 2024)
This study aims to improve students' academic achievement by implementing the TAI (Team Assisted Individualization) cooperative learning model. The method used is Classroom Action Research (CAR) conducted over two cycles. Each cycle consists of planning, action implementation, observation, and reflection stages. The subjects of this research are third-semester students totaling 32 individuals. Data were collected through observation and tests using observation sheets and test instruments. Data analysis was conducted qualitatively and quantitatively. The results of the study indicate: 1) There is a significant improvement in students' academic performance from the pre-cycle to cycle 2, indicating that the learning model used is effective in enhancing students' understanding and achievement. 2) Changes in teaching strategies successfully increased the average scores and classical mastery percentages, confirming that adjustments in teaching methods have a positive impact on students' learning outcomes. 3) The number of students who have not reached the learning targets decreased from cycle 1 to cycle 2, indicating an improvement in the quality of learning and the success of additional efforts in addressing learning challenges.